Inexpensive Green Mini Supercomputer Based on Single Board Computer Cluster - Priyambodo, T.K.; Lisan, A.W.; Riasetiawan, M. (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2018)
This work focused on building a cluster computer named Wisanggeni 01 as mini-supercomputer for high performance computing, research, and educational purposes. Wisanggeni 01 was constructed from 33 node Raspberry Pi 2. Wisanggeni 01 runs Rasbian Whezzy OS with MPICH as parallel protocol. The Wisanggeni 01 performance is optimized with overclocking. The Wisanggeni 01 performance was tested with HPL benchmark, temperature test, and power consumption test. The result indicated that the peak performance of Wisanggeni 01 are 6020 MFLOPS with N=59000 at default clock and 9943 MFLOPS with N=55000 when overclocked. Average temperature when idle is 27.1°C – 30.2°C and 31.2°C – 34.6°C when running HPL benchmark. Average temperature at overclocked mode increase 2°C higher. Maximum wattage load of Wisanggeni 01 are 110W at default clock and 125W at overclocked clock. Power consumption used are 56% Raspberry Pi, 31% switch, and 13% cooler – LED.